2021
DOI: 10.1021/acsestwater.1c00194
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose CaO2 Enhanced Arsenite Coagulation via Elevating Solution pH and Persistently Oxidizing As(III) into As(V)

Abstract: As a low-cost and commonly used technology, coagulation usually encounters two difficulties in disposing arsenite (As(III)): (1) the removal efficiency is much lower than that of arsenate (As(V)), and (2) acidic conditions are quite detrimental to As(III) removal. Calcium peroxide (CaO 2 ) possesses dual functions of oxidizing pollutant and elevating solution pH. A CaO 2 -enhanced coagulation method was thus constructed in this study, aiming to develop a versatile coagulation strategy to treat As(III) pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It is well known that arsenic removal by coagulation can be completed within 1–2 minutes. 17 Therefore, it can be concluded that the As( iii ) in UV/AA + TS system was firstly oxidized to As( v ), and then the resultant As( v ) was quickly immobilized by the coagulated flocs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that arsenic removal by coagulation can be completed within 1–2 minutes. 17 Therefore, it can be concluded that the As( iii ) in UV/AA + TS system was firstly oxidized to As( v ), and then the resultant As( v ) was quickly immobilized by the coagulated flocs.…”
Section: Resultsmentioning
confidence: 99%
“…In an oxidation–coagulation system, the oxidation of As( iii ) and coagulation removal of arsenic simultaneously occur. 17 Thus, the relationship between these two effects was investigated by determining the kinetic variations in the As( iii ) and As( v ) concentrations in solution and on the flocs. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations